THE EFFECT OF ENVIRONMENTAL PERFORMANCE ON FIRM VALUE WITH CORPORATE SOCIAL RESPONSIBILITY AS A MODERATING VARIABLE IN MANUFACTURING COMPANIES LISTED ON THE INDONESIAN STOCK EXCHANGE FOR THE PERIOD 2016-2020 - Renaldi Agata; Firdaus Rosman; Rama Bayu Nugraha; Anuar Sanusi; Suhendro Yusuf (Journal of Research in Social Science and Humanities, 2024)
Looking at environmental performance and business value through the prism of corporate social responsibility (CSR) is the focus of this study. Quantitative in nature, this research is association-based. This study will concentrate on manufacturing companies that have conducted initial public offerings on the Indonesia Stock Exchange for the past five years, from 2016 to 2020. Manufacturing companies that have participated in PROPER for the past five years will be sampled for our study. The information collected for this study comes from secondary sources. The data was examined using moderated regression analysis (MRA). This study shows that corporate social responsibility (CSR) initiatives will not be able to reduce the negative impact of environmental performance on firm value.